2021
DOI: 10.1111/ajgw.12483
|View full text |Cite
|
Sign up to set email alerts
|

Identification of optimal and novel reference genes for quantitative real‐time polymerase chain reaction analysis in grapevine

Abstract: Background and Aims Quantitative real‐time polymerase chain reaction (qRT‐PCR) has the advantages of sensitivity, specificity and repeatability, and is commonly used to investigate the expression levels of genes. The selection of appropriate endogenous reference genes is the pre‐condition for acquiring the desired results of qRT‐PCR. This study aimed to identify and screen the most suitable reference genes for grapevines. Methods and Results Three novel genes from previous transcriptomic data were selected for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Many studies on reference gene selection were reported in kiwifruit, with selected genes including TUB and ACTB combination and ACT, GAPDH, and UBQ combination [45,46,50]. In fig stems, 18s rRNA emerged as the preferred reference gene [47], In grape, RRM1 and EF-1α in combination are appropriate as internal reference genes [51]. For grape branch and leaf development processes, Ren et al [52] identified GAPDH, UBQ-1, and EF-1α1 as suitable reference genes.…”
Section: Selection Of Internal Reference Genes In Vegetative Organsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on reference gene selection were reported in kiwifruit, with selected genes including TUB and ACTB combination and ACT, GAPDH, and UBQ combination [45,46,50]. In fig stems, 18s rRNA emerged as the preferred reference gene [47], In grape, RRM1 and EF-1α in combination are appropriate as internal reference genes [51]. For grape branch and leaf development processes, Ren et al [52] identified GAPDH, UBQ-1, and EF-1α1 as suitable reference genes.…”
Section: Selection Of Internal Reference Genes In Vegetative Organsmentioning
confidence: 99%
“…UQB was also deemed suitable for the leaves of litchi [58] and apple [59]. For grape leaves, GAPDH, UBQ-1, EF-1α1, RRM1, and EF-1α combinations were found to be appropriate internal reference genes [51,52].…”
Section: Selection Of Internal Reference Genes In Vegetative Organsmentioning
confidence: 99%
“…It is generally the housekeeping gene that maintains the basic life activities of cells, such as Actin, 18s Ribosome RNA, Tublin and Ubiquitin, etc. [19,20]. However, many studies have proved that the transcription levels of the housekeeping genes may change with different species, tissues, and organs [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Two independent studies have used microarray data to search for the most stable novel reference genes of wine grape cultivars under biotic stress (i.e., infection with Plasmopara viticola and Botrytis cinerea) [64], or abiotic stress (water and heat stress) [65]. Two other studies have used RNA-Seq data to identify novel reference genes in berries of table grapes across different phenological stages and under abiotic stress [66,67]. However, no studies have used genome-wide screening to identify reference genes with stable expression across viral infection, tissue types and phenological stages.…”
Section: Introductionmentioning
confidence: 99%